2018
DOI: 10.3390/ijerph15122637
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Paracetamol by an UV/Chlorine Advanced Oxidation Process: Influencing Factors, Factorial Design, and Intermediates Identification

Abstract: The combination of a low-pressure mercury lamp and chlorine (UV/chlorine) was applied as an emerging advanced oxidation process (AOP), to examine paracetamol (PRC) degradation under different operational conditions. The results indicated that the UV/chlorine process exhibited a much faster PRC removal than the UV/H2O2 process or chlorination alone because of the great contribution of highly reactive species (•OH, •Cl, and ClO•). The PRC degradation rate constant (kobs) was accurately determined by pseudo-first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, as the amide group already occupies the para position on ACE, the chlorinations occur on the ortho positions (which is according to the negative atomic charges on C5 and C7 of ACE, Table 2). Indeed, the chlorination in ortho positions has been also reported for the treatment of ACE by the UV/HOCl process [47], supporting the high susceptibility of such position to the chlorination. NAPQI is a noxious substance, which can induce hepatic necrosis [40].…”
Section: Regions On Ace Attacked By Hocl and Possible Primary Degradation Productsmentioning
confidence: 58%
See 1 more Smart Citation
“…However, as the amide group already occupies the para position on ACE, the chlorinations occur on the ortho positions (which is according to the negative atomic charges on C5 and C7 of ACE, Table 2). Indeed, the chlorination in ortho positions has been also reported for the treatment of ACE by the UV/HOCl process [47], supporting the high susceptibility of such position to the chlorination. NAPQI is a noxious substance, which can induce hepatic necrosis [40].…”
Section: Regions On Ace Attacked By Hocl and Possible Primary Degradation Productsmentioning
confidence: 58%
“…Additionally, products of ACE chlorination have potential toxicity per se due to their organochlorinated nature. Hence, the electrolysis time could be extended to promote the further oxidation of these initial compounds, or a post-treatment with UVC light of the resultant solutions may be applied to promote the formation of other powerful oxidizing agents (such as chlorine radical and hydroxyl radical, from the homolytic cleavage of the electrogenerated HOCl [47]). It is remarked the relevance of these kinds of experiments (treatment at long times or combination with UVC light).…”
Section: Regions On Ace Attacked By Hocl and Possible Primary Degradation Productsmentioning
confidence: 99%
“…In the case of phenolic compounds of salbutamol, ractopamine, and bisphenol A, these chemicals are transformed into the corresponding phenoxides with increasing pH, which are richer in electrons and more reactive with RCS [23]. Paracetamol degradation is also enhanced at pH higher than 7.0 due to higher reactivity of ClO − with paracetamol than that of HOCl [81]. Thus, both dissociation processes and selectivity of reactive species reactions with a pollutant also influence the pH dependency of the performance of UV/chlorine AOPs.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Dao et al reported that the degradation rate of paracetamol in a tap water and in a surface water was 54 and 67% lower than that in deionized water, respectively, and the lower degradation efficiency of paracetamol in real waters resulted from higher concentrations of NH 4 + , Cl − , SO 4 2− , phosphate, inorganic carbon (e.g. HCO 3 − ), and especially DOM [81]. Among various solutes in real waters inorganic carbon and DOM are thought to be responsible for the inhibition effect, which act as radical scavengers and decrease the effective radical concentration available to react with contaminants [75,83].…”
Section: Applicationsmentioning
confidence: 99%
“…Currently, wastewater pollution has become one of the most significant environmental problems around the world. Pharmaceutically active compounds, which is used for treating humans and animals, are usually polar molecules and soluble in water. , They have been classified as emerging contaminants because of several disadvantageous physicochemical properties for the sustainability of water environment and ecosystem, such as persistence, microbial resistance, and bioaccumulation in the food chain. In addition, their existence represents a threat to both public health and environment with long-term potential hazardous effects on aquatic fauna and flora owing to increasing consumption and continuous input to the environment. , Among numerous pharmaceutical compounds detected in waste bodies, diclofenac (DCF; a nonsteroidal anti-inflammatory drug) is commonly used in human medical care as analgesic, antiarthritic, and antirheumatic compounds. , This drug can be ubiquitously found in urban wastewater, surface water, and drinking water sources that might result from the remaining washing-off from the skin or clothes. , Even very low doses of the as-mentioned drugs can lead to water pollution and unfavorable effects on the endocrine system. ,, Therefore, the elimination of harmful endocrine-disrupting compounds from waste bodies has become a prominent field of study . In recent years, the application of porous materials for eliminating different organic pollutants from wastewater has brought about satisfactory results at room temperature and atmospheric pressure using catalytic wet peroxide oxidation technology .…”
Section: Introductionmentioning
confidence: 99%